Pattern of utilization of blood and blood components in obstetrics at a tertiary care center: a cross-sectional study - Jacob, Alpana; Goyal, Sunita; Dhar, Tapasya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Blood transfusion is an essential lifesaving component in obstetrics. Extra blood loss in pregnancy can occur due to various gestational disorders and complications during labour and delivery. Reduction in maternal morbidity and mortality has been observed by increased use of comprehensive emergency obstetrics care in which blood transfusion has achieved recognition as one of the important components. In a developing country like India, the need for well maintained and readily available blood and transfusion services becomes paramount to decrease maternal morbidity and mortality. We wanted to determine the clinical characteristics and indication of blood transfusion in obstetrics and also determine any adverse blood transfusion reaction. Methods: This cross-sectional study was conducted in the department of obstetrics and gynaecology, Christian medical college, Ludhiana for a period of eighteen months from 15th October 2018. The study group included all the antenatal and postnatal patients up to 6 weeks postpartum who were admitted in the obstetric unit, requiring blood or component transfusions. Clinical characteristics, indication of blood transfusion and any adverse blood transfusion reaction were recorded. Results: In our study, about 7.84% of obstetric admission required blood and blood components. Most common indication for blood transfusion was anaemia either during antenatal or during postnatal period (33.91%). Majority of the patients were unbooked antenatally (63.91%) and were multiparous (93.91%). 4 or more blood transfusions were given in 28.26% of cases. Conclusions: Blood transfusion is live saving measure in many obstetric patients. Blood transfusion is an essential component of emergency obstetric care and appropriate blood transfusion significantly reduces maternal mortality. Severe anaemia is the most common condition requiring blood transfusion, which may be chronic due to nutritional deficiency or following acute blood loss, followed by postpartum haemorrhage, placental abruption and placenta previa. Availability of transfusion facility and blood products in obstetric care setting in peripheral health centres can reduce need for referral of patients and indirectly reduce the maternal morbidity and mortality.